The paradox between low shock-stage and evidence for compaction in CM carbonaceous chondrites explained by multiple low-intensity impacts - Lindgren, Paula; Hanna, Romy D.; Dobson, Katherine J.; Tomkinson, Tim; Lee, Martin R. (Geochimica et Cosmochimica Acta, 2015)
Petrographic analysis of eight CM carbonaceous chondrites (EET 96029, LAP 031166, LON 94101, MET 01072, Murchison, Murray, SCO 06043, QUE 93005) by electron imaging and diffraction, and X-ray computed tomography, reveals that six of them have a petrofabric defined by shock flattened chondrules. With the exception of Murchison, those CMs that have a strong petrofabric also contain open or mineralized fractures, indicating that tensional stresses accompanying the impacts were sufficient to locally exceed the yield strength of the meteorite matrix. The CMs studied span a wide range of petrologic subtypes, and in common with Rubin (2012) we find that the strength of their petrofabrics increases with their degree of aqueous alteration. This correspondence suggests that impacts were responsible for enhancing alteration, probably because the fracture networks they formed tapped fluid reservoirs elsewhere in the parent body. Two meteorites that do not fit this pattern are MET 01072 and Murchison; both have a strong petrofabric but are relatively unaltered. In the case of MET 01072, impact deformation is likely to have postdated parent body aqueous activity. The same may also be true for Murchison, but as this meteorite also lacks fractures and veins, its chondrules were most likely flattened by multiple low intensity impacts. Multiphase deformation of Murchison is also revealed by the microstructures of calcite grains, and chondrule-defined petrofabrics as revealed by X-ray computed tomography. The contradiction between the commonplace evidence for impact-deformation of CMs and their low shock stages (most belong to S1) can be explained by most if not all having been exposed to multiple low intensity (i.e., <5. GPa) shock events. Aqueous alteration was enhanced by those impacts that were of sufficient intensity to open high permeability fracture networks that could connect to fluid reservoirs.